2014
DOI: 10.1007/s12149-014-0888-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of myocardial blood flow using 201Tl SPECT and population-based input function

Abstract: This study demonstrated that the proposed technique based on a STD-IF and one-point blood sample provided hemodynamically reasonable global MBF values and the regional MBF values comparable to those with IND-IFs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Several investigators have already validated the SIF approach for human use. 10 , 11 , 12 , 13 Furthermore, a study reported the application of the SIF approach to CMRGlc measurement in small animals with one or two arterial blood samples for scaling the SIF, thereby allowing for accurate estimation of the AIF in each subject's level. 14 It is thus indicated that the SIF technique with a few arterial blood samples may serve as a simplified quantification method of CMRGlc in small animals.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigators have already validated the SIF approach for human use. 10 , 11 , 12 , 13 Furthermore, a study reported the application of the SIF approach to CMRGlc measurement in small animals with one or two arterial blood samples for scaling the SIF, thereby allowing for accurate estimation of the AIF in each subject's level. 14 It is thus indicated that the SIF technique with a few arterial blood samples may serve as a simplified quantification method of CMRGlc in small animals.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike a dedicated cardiac SPECT camera with solid-state detectors, the conventional two-headed SPECT camera is readily available and widely used in the nuclear medicine community; hence it is possible to reproduce the method on clinically installed systems. 23-25 …”
Section: Discussionmentioning
confidence: 99%
“…Global MBF was derived from the corresponding K1 values using the Renkin-Crone equation for 201 Tl [20,21]. MBF value was obtained from the K1 value and corrected for the first-pass extraction fraction (EF) and hematocrit (Hct) using the equation MBF = K1*/EF, where EF = 1-0.57*e À1.02/MBF and K1* = K1/(1-Hct) [22,23]. MPR was then computed as a ratio of the stress to rest MBF values (MPR = stress MBF/rest MBF).…”
Section: Spect Images and Quantitative Analysismentioning
confidence: 99%